Remediation of Azure A Dye from Aqueous Solution by Using Surface-Modified Coal Fly Ash Extracted Ferrospheres by Mineral Acids and Toxicity Assessment - Virendra Kumar Yadav; Gajendra Kumar Inwati; Daoud Ali; G. Gnanamoorthy; Sweta Parimita Bera; Samreen Heena Khan; Nisha Choudhary; Gokhlesh Kumar; Tejulal Prasad Chaurasia; Anup Basnet (Adsorption Science & Technology)
The Indian coal fly ash (CFA) is composed of 5-15% ferrous fractions. The variation in percentage depends on the source of coal and the operating conditions of the thermal power plants. The present research work reports the recovery of ferrous particles from CFA by the wet magnetic separation method. The morphological, elemental, and chemical properties of the extracted ferrous fractions were analyzed. In order to achieve surface-modified ferrospheres, the extracted ferrospheres were treated with concentrated HCl followed by sonication. The instrumental analysis reported the ferrous composition is around 16% by weight and belongs to class F. The toxicity of CFA was determined on normal human lung (BEAS-2B) cells using MTS assay. The results showed that CFA’s induced cell toxicity in a dose-dependent manner. The ferrous particles were spherically shaped with various sizes ranging from 200 nm to 7000 nm. It was crystalline in nature and is a mixture of hematite and magnetite. The particles were found to be associated with alumina, silica, oxygen, and traces of Ca, Mg, Ti, and C. The surface-modified ferrospheres were used for the remediation of Azure A dye by batch adsorption study. The removal percentage of dye was 25.03%, within 30 minutes at neutral pH, i.e., 7.2. The surface-modified ferrospheres show potential as an alternate, more economical, and reusable adsorbent for the remediation of Azure A dye in the industries or in common effluent treatment plants. Moreover, the recovery of surface-modified ferrospheres using an external magnet and the reuse of the particles make the material much economical for dye removal at an industrial scale.